Multidimensional intelligence on teacher performance in elementary schools - Siswanto, Romi; Abidin, Achmad Anwar; Kadarisman, Kadarisman; Jaya, Fitra; Sucipto, Sucipto; Yati, Yati (Universitas Jambi, Indonesia, 2025)
This research explored the influence of multidimensional intelligence, including emotional, social, spiritual, and academic intelligence, on the performance of elementary school teachers in Indonesia. Five hundred teachers from various regions were selected as samples using stratified random sampling techniques. The survey method was used to collect data, and multiple linear regression analysis was applied to determine the influence of each intelligence dimension on teacher performance. The results indicated that all dimensions of intelligence positively impacted teacher performance, with academic intelligence having the most dominant effect (coefficient 0.295), followed by social intelligence (0.182), emotional intelligence (0.170), and spiritual intelligence (0.086). These findings indicate the importance of a holistic approach to improving teacher performance, focusing on strengthening academic and social intelligence. The research also recommends that teacher development policies pay more attention to multidimensional intelligence in training programs. Future research should expand the scope by considering factors such as work environment and intrinsic motivation that may affect teacher performance.